Mobilebackup Software - SRIDEVI BHIMA (2004)
INTERNAL GUIDE : Patil Shantakumar B. EXTERNAL GUIDE: Venkatesh P C USN No : 1MJ03SCS13 CARRIED OUT AT : ComCreation Technologies (P) Bangalore-560 076 ACC NO : PC18
Keywords: M.Tech Computer Science